Social Comparison and Quarter-Life Crisis in Generation Z: A Study of Instagram Users - Maharani, Pande Ketut Gita Kusuma; Merida, Sarita Candra (Universitas Negeri Semarang, 2025)
Generation Z was born and grew up during rapid technological development. Instagram, one of the social media platforms often used by Generation Z, provides an opportunity for social comparison, which can contribute to triggering and worsening quarter-life crises. This study aims to determine the relationship between social comparison and quarter-life crisis in Generation Z active Instagram users in Bekasi City. This research uses a quantitative approach with a correlational study method. The sample comprised 164 respondents aged 20-28 years who were selected using a purposive sampling technique. The research instruments included the INCOM scale, used to measure social comparison and a modified Quarter-Life Crisis scale. The results of data analysis using the Pearson product-moment correlation test showed a significant positive correlation between social comparison and quarter-life crisis (r = 0.757; p < 0.05). The results indicate that the higher the tendency of individuals to do social comparison, the higher the level of quarter-life crisis experienced. This finding reinforces the role of social media, especially Instagram, in triggering and exacerbating the quarter-life crisis in Generation Z through social comparison. Consequently, Generation Z must focus on their goals and improve their time management skills when using Instagram.